2016
DOI: 10.1073/pnas.1614538113
|View full text |Cite
|
Sign up to set email alerts
|

Graded activation and free energy landscapes of a muscarinic G-protein–coupled receptor

Abstract: G-protein-coupled receptors (GPCRs) recognize ligands of widely different efficacies, from inverse to partial and full agonists, which transduce cellular signals at differentiated levels. However, the mechanism of such graded activation remains unclear. Using the Gaussian accelerated molecular dynamics (GaMD) method that enables both unconstrained enhanced sampling and free energy calculation, we have performed extensive GaMD simulations (∼19 μs in total) to investigate structural dynamics of the M 2 muscarini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
175
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 149 publications
(184 citation statements)
references
References 36 publications
9
175
0
Order By: Relevance
“…Along this pathway, 24 equally distributed frames-including the crystallographic states-were subjected to conventional MD and GaMD simulations for a total of ∼15 μs with the aim of rigorously characterizing the conformational dynamics of the complex over a long timescale, made possible through the application of enhanced sampling (SI Appendix) (15,16,19). Intermolecular FRET distances have been used to characterize the conformational states of Cas9 during the dynamics ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Along this pathway, 24 equally distributed frames-including the crystallographic states-were subjected to conventional MD and GaMD simulations for a total of ∼15 μs with the aim of rigorously characterizing the conformational dynamics of the complex over a long timescale, made possible through the application of enhanced sampling (SI Appendix) (15,16,19). Intermolecular FRET distances have been used to characterize the conformational states of Cas9 during the dynamics ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Here, we characterize the dynamics of the activation pathway of the Cas9 endonuclease through extensive enhanced MD simulations (∼15 μs in length), using a GaMD methodology (18), which allows unconstrained sampling and accurate reconstruction of the free-energy profiles and probes long timescale events over hundreds of microseconds to milliseconds (19,20).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent simulations on a variety of GPCRs have shown that the extracellular vestibule of the receptor can pre-orient the ligand [34][35][36][37][38][39] and thus provide a well-defined extracellular end-point for docking pathways, and thus simplifying the path-sampling task, often by a form of electrostatic focusing 40 but also by a simple mechanical effect in which part of the ligand is anchored, Additionally, to speed up the sampling, this approach can be easily combined with multiplereplica metadynamics approaches, such as parallel tempering 29 or the multiple-walker technique, 39 which uses several "walkers" to converge one free-energy profile. In our case, we found the trivially parallelizable (and asynchronous) multiple-walker approach more suitable as it is very flexible (the number of replicas can be dynamically changed to use the available resources) and ensures maximum computational efficiency even on non-homogenous clusters.…”
Section: A General and Effective Collective Variablementioning
confidence: 99%
“…The explosion of available crystal structures of GPCRs has transformed drug design strategies for the GPCR monomer model, and although crystal structures of homodimers (66)(67) and homo-oligomers (68) have been identified, heteromeric structures would provide unprecedented information, not only on interfaces, but unique heteromer-specific targeting sites for structure-based drug discovery. With the generation of antibodies that target GPCR heteromers and the use of nanobodies in GPCR research (69)(70)(71)(72)(73)(74)(75)(76), there is a real technical possibility of creating tools to aid stabilisation of such structures for crystallization. Likewise there is increase interested in immunotherapy pathways, particularly in cancer, and whilst there are no current approved GPCR antibody drugs, antibodies specific to GPCR heteromers have been generated (77).…”
Section: Specific Activation Of Gpcr Heteromersmentioning
confidence: 99%